Smoking-related bladder cancer burden from 1990 to 2021: An age-period-cohort analysis of the global burden of disease study - Qingqing Yu; Bing Li; Hao Lin; Chao Sun; Xinyue Yang; Zhiqiang Zhang (Tobacco Induced Diseases)
Introduction Bladder cancer is common in the elderly, with smoking as a major risk factor. This study assesses the global burden of bladder cancer attributable to smoking, using data from 204 countries and regions (1990–2021).